BIOGEOGRAPHY AND EVOLUTION OF PALEOZOIC BRYOZOANS OF THE GENUS RHOMBOTRYPELLA - Naimark E.B.; Gorjunova R.V. (My University, 2004)
The spatial variations of the genus Rhombotrypella throughout its existence are traced. This genus emerged in the Middle Carboniferous, when it was restricted to the tropical zone. Subsequently, it inhabited both of the polar zones in the Early Permian and isolated basins of the boreal zone in the Late Permian. The pattern of the spatial variations of Rhombotrypella species is consistent with that of other coeval marine invertebrates (mollusks and brachiopods). The variability of nine morphological characters of the species of this genus is analyzed. Two characters show geographic variability, five characters show temporal trends. The phylogeny of the genus is reconstructed based on the geographic ranges of its species and evolutionary changes in species characters.
Keywords: Paleozoic; Paleozoic; Палеозой